Investigating Work Technology in Road Traffic - Kolenc, Jurij; Zgonik, Miran (Promet - Traffic&Transportation)
The study of the organisation and technology of work intraffic in general as well as in road craffic is conducted from differentstandpoints. Relevant scientific and expert literaturedeals with different approaches to the above study, which generatesconfusion among the experts who want the organisationand 1echnology of work in road lraffic to be based on thegrounds of scientific organisation of work. The paper deals withthe aspeCl of study which is based on the theory of scientific organisationand technology of work as well as its implementationin road traffic. The paper analysis especially the methodsby which human work and influences upon it in road traffic arestudied. The results of the said aspect of study show that it ispossible 10 rationalise work, improve the exploitation indexesand, in general, improve the efficiency of existing organisationand technology of road traffic as a whole. Using the same aspectof study a new organisation and technology of road trafficcan also be established and optimised.